An Analysis Of Students’ Difficulties In Reading Comprehension At 8TH Grade Student In Smp N 1 Dimembe - PANDEAN, ALVANDO R.; Oroh, Elisabeth Z.; Kumayas, Tirza A. (Program Studi Pendidikan Bahasa Inggris, 2024)
The purpose of this study is to find out, what are the students’ difficulties in reading comprehension at 8th grade student in SMP N 1 Dimembe. The researcher used qualitative research with a qualitative descriptive design involving 29 student of class 8th C and for the interviews the researcher took six students as the informants. Information collection was carried out through observation, interviews, and documentation. There are 3 stages of data analysis, first is data condensation, second, data display, third, drawing and verifying conclusions.In analyzing the data, the researcher finds out the difficulty by the student in reading comprehension namely: difficulties to understanding the meaning of the word, the difficulties to understand the long sentence within the text, difficulties in understanding the main idea, difficulties in understanding the grammar, and difficulties to create the inferences. After analyzing the data, the results showed that students still had difficulty in reading